The Disability and Wellbeing Monitoring Framework: data, data gaps, and policy implications - Nicola Fortune; Hannah Badland; Shane Clifton; Eric Emerson; Jerome Rachele; Roger J. Stancliffe; Qingsheng Zhou; Gwynnyth Llewellyn (Elsevier, 2020)
Abstract Objective: To develop a framework and indicators to monitor inequalities in health and the social determinants of health for Australians with disability. Methods: The development drew on existing frameworks and input from people with lived experience of disability. Results: The Disability and Wellbeing Monitoring Framework has 19 domains. Australian national data are available for 73% of the 128 indicators in these domains. Data gaps and limitations include the absence of national data and the absence of disability identifiers in some data sources. Conclusions: The framework will be used to report baseline data for people with and without disability and to monitor inequalities over time in Australia. It will also be used to locate policy priorities and focus efforts to address data gaps. Implications for public health: Inequality between people with and without disability in relation to health and the social determinants of health is a public health issue that warrants greater attention than it has received to date. The framework provides a robust, evidence‐informed tool to address the health inequalities of people with disability, inform the development of effective policy and practice responses, and monitor change over time.